Pilot Scale Hollow Fiber Pervaporation System for Phenol Recycling from Coal to Chemical Wastewater - Jie, Yao; Dandan, Zhang; Chao, Cai; Hongxia, Guo; Bangjun, Han; Yahong, Han; Zhenao, Gu; Shuren, Yang; Hong, You; Ziwei, Du; Agtmaal, Sjack van; Chunhui, Feng (Journal of Membrane and Separation Technology, 2014)
Polydimethylsiloxane (PDMS)/Polyvinylidene fluoride (PVDF) hollow fiber composite membrane was prepared by dynamic negative pressure method to treat coal to chemical wastewater containing high concentration of phenol, in which PVDF hollow fiber membrane acts as base membrane and PDMS as modified membrane. In the pilot scale experiment, the influence of aeration rate, temperature, flow rate, pressure under membrane on phenol removal efficiency were investigated and operating parameter optimized. At temperature 70℃, flow rate of 150 L/h, pressure under membrane 5 KPa, gas-water ratio 0.3, 75 L coal to chemical wastewater containing phenol fluctuated between 1600 and 1800 mg/L was treated for 6h, and phenol removal efficiency reached 72%. The system ran stably for 120 h and performed well, phenol removal efficiency being kept more than 60%.